(untitled) (Herald of the National Children’s Medical Center, 2024)
Introduction. Surgical diseases of the pancreas (pancreas) are relevant in pediatric surgery due to their relative rarity and complexity of diagnosis. In the last decade, descriptions of cases of pancreatic pathology requiring surgical treatment have become more frequent. There are publications in the literature aimed at improving diagnostic and therapeutic techniques, the introduction of minimally invasive methods of treatment in children.